The Implementation of Knowledge Strategy-Based Entrepreneurial Capacity to Achieve Sustainable Competitive Advantage - Widodo, Widodo (International Research Journal of Business Studies, 2013)
This study aims to develop a model of knowledge strategy-based entrepreneurial capacity to achieve sustainable competitiveadvantage of rurol banking in Central Java province. The sampling method is ‘‘Purposive sampling’’ by considering the characteristics of the population items, namely: operational experience for at least 5 years and representatives of each area of rurol banking in Semarang, Surakarta and Purwokerto. Then, the sample size is 150 of 251 (59.7%) of top managers of rurol banking. To analyze the data in this study, it used the Structural Equation Modeling (SEM), of the, AMOS software package. The findings of this study explain that 1). The first step in promoting a sustainable competitive advantage through knowledge sharing is by prioritizing the quality of interaction, willingness and ability. 2). Efforts to improve a sustainable competitive advantage through knowledge exploitation built by knowledge sharing are by prioritizing to actively accept changes and introduction, solve problems together, use and combine new knowledge in operation. 3). Efforts to improve a sustainable competitive advantage through the knowledge exploitation built by risk-taking are by prioritizing a strong tendency for high-risk projects (with the possibility of gaining high-return), a high courage for the actions necessary to achieve the goal, having an aggressive attitude to optimize the possibility of utilizing existing potential opportunities and enjoying the challenge of the risk situation. 4). Efforts to improve a sustainable competitive advantage through knowledge exploitation built by a pro-active are by prioritizing to anticipate problem more quickly than competitors, future oriented, addressed by technology, launching product selectively and systematically search for new ideas. 5). Efforts to improve a sustainable competitive advantage through knowledge exploitation built by the innovativeness are by prioritizing the speed of developing products, the implementation of new technology and market development.